Aplikasi Evidence Based Nursing Hand-Held Fan Therapy pada Pasien Kanker Paru (Journal of Telenursing (JOTING), 2023)
This study aims to prove the application of evidence-based nursing hand-held fan therapy for dyspnea in lung cancer patients. The method used was pre-experimental, with a sample size of 10 lung cancer patients. The results of the study showed that there was a significant effect of the application of hand-held fan therapy on dyspnea, respiratory rate, and SpO2 in lung cancer patients (p